The Selective Rat Toxicant Norbormide Blocks KATP Channels in Smooth Muscle Cells But Not in Insulin-Secreting Cells - Saponara, Simona; Fusi, Fabio; Spiga, Ottavia; Trezza, Alfonso; Hopkins, Brian; Brimble, Margaret A.; Rennison, David; Bova, Sergio (Frontiers in Pharmacology, 2019)
Norbormide is a toxicant selective for rats in which it induces a widespread vasoconstriction. In a recent paper, we hypothesized a role of ATP-sensitive potassium (KATP) channels in norbormide-induced vasoconstriction. The current study was undertaken to verify this hypothesis by comparing the effects of norbormide with those of glibenclamide, a known KATP channel blocker. The whole-cell patch-clamp method was used to record KATP currents in myocytes freshly isolated from the rat and mouse caudal artery and from the rat gastric fundus, as well as in insulin-secreting pancreatic beta cells (INS-1 cells). Smooth muscle contractile function was assessed on either rat caudal artery rings or gastric fundus strips. Molecular modelling and docking simulation to KATP channel proteins were investigated in silico. Both norbormide (a racemic mixture of endo and exo isomers) and glibenclamide inhibited KATP currents in rat and mouse caudal artery myocytes, as well as in gastric fundus smooth muscle cells. In rat INS-1 cells, only glibenclamide blocked KATP channels, whereas norbormide was ineffective. The inhibitory effect of norbormide in rat caudal artery myocytes was not stereo-specific as both the endo isomers (active as vasoconstrictor) and the exo isomers (inactive as vasoconstrictor) had similar inhibitory activity. In rat caudal artery rings, norbormide-induced contraction was partially reverted by the KATP channel opener pinacidil. Computational approaches indicated the SUR subunit of KATP channels as the binding site for norbormide. KATP channel inhibition may play a role in norbormide-induced vasoconstriction, but does not explain the species-, tissue-, and stereo-selectivity of its constricting activity. The lack of effect in INS-1 cells suggests a potential selectivity of norbormide for smooth muscle KATP channels.